EFFICACY OF SCHOOL-BASED ORAL HEALTH PROMOTION: A NARRATIVE REVIEW - Stanislawski, Dominik; Borek, Natalia; Gałązka, Julia; Stopa, Ewa; Krupa, Hanna; Kędrak, Magdalena; Wieczorek, Zofia; Miśkiewicz, Emilia; Jabłońska-Trzosek, Wiktoria; Pochwalski, Jakub (International Journal of Innovative Technologies in Social Science, 2026)
Childhood oral diseases, such as dental caries, remain globally prevalent. This narrative review synthesizes evidence on the efficacy of school-based oral health promotion programs for children and adolescents (aged 5–18), focusing on knowledge, oral hygiene, and caries outcomes. A literature search of PubMed/MEDLINE, Scopus, and Google Scholar was conducted for English-language systematic reviews, meta-analyses, and clinical trials evaluating school-based preventive interventions. School-based programs consistently improve oral health knowledge and achieve short-term plaque reductions; however, education alone shows limited long-term clinical impact. Sustained clinical outcomes, specifically caries reduction, require multicomponent programs integrating supervised fluoride delivery, parental involvement, and teacher-led reinforcement. Currently, the certainty of evidence remains low to moderate due to study heterogeneity and short follow-up periods. School-based oral health promotion is a viable public health strategy when implemented as a sustained, multicomponent initiative extending beyond the classroom. Future research should prioritize cost-effectiveness, standardized measures, and longer follow-ups, particularly in low- and middle-income settings.